ANTIMICROBIAL RESISTANCE IN GRAM-POSTIVIE BACTERIA ISOLATED FROM BLOOD CULTURE - Jovchevski, Radomir; Cekovska, Zaklina; Kovacheva-Trpkovska, Danica; Kostovski, Marko; Labachevska-Gjatovska, Liljana; Krsteva, Nadica; Mihajlov, Kiril; Jurhar-Pavlova, Maja; Grdanoska, Tatjana (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
Blood cultures are essential in diagnosing the existence of bacteria in the blood and they continue to be the gold standard for the diagnosis of septicemia. From Gram-positive bacteria, Staphylococcus aureus and Enterococcus spp . are the most common bacteria causing sepsis and septic shock. They are the leading causes of hospital-acquired infections globally. Aim of the paper was to identify Staphylococcus aureus and Enterococcus spp . from hemoculture and to determine their susceptibility to antibiotics. Blood samples from hospitalized patients admitted for routine laboratory testing at the Institute of Microbiology from January 2023 to December 2023 were included in the study. Blood cultures bottles were incubated in automated Bact/Alert system. Isolated colonies were identified using automated VITEK 2 Compact system. MSSA and MRSA were isolated in 48.2% and 51.8% respectively. All isolates 100% were resistant to penicillin. Intermediate sensitivity to levofloxacin 92%, 60% and ciprofloxacin 96%, 64% was observed in MSSA and MRSA strains. Resistance to gentamicin of 63% was seen in MSSA isolates. Non-VRE and VRE were isolated in 67% and 33% respectively. Non-VRE strains had higher resistance towards gentamicin 77%, streptomycin 66%. VRE strains were resistant to gentamicin 93%, ampicillin 85%. Our findings give analysis of Gram-positive bacteria isolated from hemoculture and their resistance pattern. The findings give clinicians an insight for the right treatment option. Keywords: Gram-positive bacteria, blood culture, antimicrobial resistance.